2015
DOI: 10.1007/s11906-015-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Pregnancy: Natural History and Treatment Options

Abstract: Hypertensive disorders of pregnancy affect approximately 5-10% of all maternities and are major contributors of maternal and neonatal morbidity and mortality worldwide. This group of disorders encompasses chronic hypertension, as well as conditions that arise de novo in pregnancy: gestational hypertension and pre-eclampsia. The latter group is thought to be part of the same continuum but with arbitrary division. Research into the aetiology of hypertension in pregnancy have largely been focused on pre-eclampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 164 publications
(154 reference statements)
1
28
0
Order By: Relevance
“…Regarding hemorrhage and high blood pressure, studies have reported an increased risk of perinatal death 25,26 , prematurity, low birth weight, and asphyxia at birth 15 among infants of mothers with hypertension in pregnancy, still a common condition during pregnancy 27,28 , and of mothers with vaginal hemorrhage prior to labor 17,29 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hemorrhage and high blood pressure, studies have reported an increased risk of perinatal death 25,26 , prematurity, low birth weight, and asphyxia at birth 15 among infants of mothers with hypertension in pregnancy, still a common condition during pregnancy 27,28 , and of mothers with vaginal hemorrhage prior to labor 17,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of Pre-Eclampsia was based on the American Congress of Obstetricians and Gynecologists (ACOG) and National High Blood Pressure Education Program (NHBPEP) criteria (5,13); patients with a sitting diastolic and systolic blood pressure of 90 and 140 mmHg, respectively, at least twice over a 6-hour interval and either proteinuria greater than 300 mg in 24-hour urine or a ≥ 1+ dipstick result were deemed as having mild Pre-Eclampsia. Patients with a systolic blood pressure of 160 and diastolic pressure of 110 mmHg or higher at the time of admission, with more than 5 g of protein in their 24-hour urine, and who had received magnesium sulfate (MgSO 4 ) treatment were considered to have severe Pre-Eclampsia.…”
Section: Methodsmentioning
confidence: 99%
“…The next report of the World Health Organization (WHO) indicated the condition as second most common cause of maternal death: 18% of deaths in mothers are linked to hypertension [3]. In Turkey, 13.7% of deaths during pregnancy are due to eclampsia, while 18.4% of maternal deaths are listed as being due to a combination including edema, proteinuria and hypertension; eclampsia is thus the second most common cause of maternal death in Turkey [4]. Pre-Eclampsia is defined as hypertension (BP >140/90 mmHg) associated with proteinuria past the 20th week of pregnancy and is classified as a pregnancy-induced hypertension [5].…”
Section: Introductionmentioning
confidence: 99%
“…Preconceptional obesity elevates the risk of gestational diabetes (GDM), gestational hypertension (GH), preeclampsia (PE) and deep venous thromboembolism (DVT), all of which are related to higher maternal morbidity rates postpartum [8,14,143,149]. A previous study assessed metabolic complications in relation to prepregnancy overweight and obesity (BMI ≥ 30 kg/m 2 ) 10 years postpartum in premenopausal Chilean women.…”
Section: Maternal Healthmentioning
confidence: 99%
“…GH increases both maternal and foetal mortality with a 5-and 3-fold higher risk for PE and stillbirth, respectively [145]. PE, typically a late pregnancy or post-delivery syndrome characterised by new onset of hypertension and proteinuria, can often appear superimposed on established gestational or prior hypertension, and is frequently observed on a background of pre-existing maternal morbidities, including obesity [149]. Obese pregnant women are estimated to be at 3-10 times higher risk of PE [14].…”
Section: Maternal Healthmentioning
confidence: 99%